2020
DOI: 10.22541/au.158999391.14810998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical utility of local impedance monitoring during pulmonary vein isolation

Abstract: Introduction: A novel ablation catheter that can measure local impedance (LI) was recently launched. We aimed to explore target LI measurements at each radiofrequency application (RFA) for creating sufficient ablation lesions during pulmonary vein (PV) isolation. Methods: This prospective study included 15 consecutive patients scheduled to undergo an initial ablation of paroxysmal atrial fibrillation (AF). Circumferential ablation around both ipsilateral PVs was performed using a 4-mm irrigated ablation cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…As previously described, a nonstimulatory alternating current (5.0 μA, 14.5 kHz) was delivered between the tip and the proximal ring to create a local potential field. [7][8][9][10] Voltage was measured between the tip electrode and the distal ring. LI was calculated by dividing the voltage by the nonstimulatory current.…”
Section: Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…As previously described, a nonstimulatory alternating current (5.0 μA, 14.5 kHz) was delivered between the tip and the proximal ring to create a local potential field. [7][8][9][10] Voltage was measured between the tip electrode and the distal ring. LI was calculated by dividing the voltage by the nonstimulatory current.…”
Section: Measurementmentioning
confidence: 99%
“…Several studies have reported that the magnitude of LI drop predicted acute PVI segment block, which is similar to our results. 7,8 Das et al 7 reported that the optimal LI drop cut-off value for the anterior/roof segments and that for the posterior/inferior segments were 16.1 and 12.3 Ω, respectively. Masuda et al 8 reported that LI drop of 13.4 Ω predicted acute PV-LA conduction block.…”
Section: Drop At Pvi Segment Block Sitesmentioning
confidence: 99%
See 3 more Smart Citations